Table of Derivatives

Download as pdf or txt
Download as pdf or txt
You are on page 1of 5

Tables of derivatives

I. Basic rules of dierentiation


Suppose that there exist u 0 (x) and v 0 (x) for any x ∈ D ⊆ R. Then for x ∈ D hold
the formulas:

1. c 0 = 0, (c = const), x 0 = 1 ;

2. (u(x) ± v(x)) 0 = u 0 (x) ± v 0 (x)  the sum rule;

3. (c.u(x)) 0 = c.u 0 (x) (c = const);

4. (u(x).v(x)) 0 = u 0 (x).v(x) + u(x).v 0 (x)  the product rule;


0
u 0 (x).v(x) − u(x).v 0 (x)

u(x)
5. =  the quotient rule;
v(x) v 2 (x)
6. If the function u = u(x) is dierentiable on the set D, and the function y = f (u) is
dierentiable on the set G = u(D), then the composite function y(x) = f (u(x)) is
dierentiable on the set D and holds the formula

y 0 (x) = f 0 (u) .u 0 (x), x ∈ D,

called formula for derivative of a composition of functions, or the chain rule.


II. Dierential of function. Properties
Let exists y 0 (x), x ∈ D. The expression

d y(x) = y 0 (x).dx, where dx = ∆x = h 6= 0

is the variation of the independent variable x, ( also called dierential of the indepen-
dent variable ), is called rst dierential of y. In this denotations the derivative can
be written as a quotient of dierentials of y and x ( denotation of Leibniz ):

dy
y 0 (x) = .
dx
Dierential possesses the following properties:

1. dc = c0 .dx = 0, (c = const) ;

2. d(u(x) ± v(x)) = (u(x) ± v(x)) 0 .dx = u 0 (x).dx ± v 0 (x).dx = du(x) ± dv(x);

3. d(c.u(x)) 0 = (c.u 0 (x)).dx = c.du(x) (c = const);

4. d(a.u(x) + c) = (a.u(x) + c) 0 .dx = a.u 0 (x)dx = a.du(x), where a and c are arbitrary
constants;

5. d(u(x).v(x)) = (u(x).v(x)) 0 .dx = (u 0 (x).v(x) + u(x).v 0 (x)).dx = v(x).du(x) +


u(x).dv(x);
  0
u (x).v(x) − u(x).v 0 (x)
 
u(x) v(x).du(x) − u(x).dv(x)
6. d = dx = ;
v(x) v 2 (x) v 2 (x)

1
7. The dierential of composite function y(x) = f (u(x)) is

dy(x) = (f (u(x))) 0 .dx = f 0 (u) .u 0 (x).dx = f 0 (u(x)) .du(x).

III. Derivative of a function represented parametrically


Let ϕ(t) and ψ(t) be dierentiable functions, dened on (α, β), and ϕ 0 (t) 6= 0 on this
interval. If the system of equations

x = ϕ(t), y = ψ(t), t ∈ (α, β)

denes y as a single-valued continuous function of x, then there exists a derivative y 0 (x)


and
dy y 0 (t).dt y 0 (t)
y 0 (x) = = 0 = 0 , t ∈ (α, β).
dx x (t).dt x (t)
IV. Dierentiation of basic elementary functions
1. (ex ) 0 = ex , x ∈ R ;
1
2. (ln |x|) 0 = , x 6= 0;
x
3. (xα ) 0 = α.xα−1 , α = const;

4. (ax ) 0 = ax . ln a, x ∈ R, a = const, a > 0, a 6= 1;


1
5. (loga |x|) 0 = , x 6= 0;
x. ln a
6. (cos x) 0 = − sin x, x ∈ R;

7. (sin x) 0 = cos x, x ∈ R;
1 π
8. (tg x) 0 = 2
, x 6= (2k + 1) , k = 0, ±1, ±2, . . .;
cos x 2
1
9. (ctg x) 0 = − , x 6= kπ, k = 0, ±1, ±2, . . .;
sin2 x
1
10. (arcsin x) 0 = √ , x ∈ (−1, 1);
1 − x2
1
11. (arccos x) 0 = − √ , x ∈ (−1, 1);
1 − x2
1
12. (arctg x) 0 = , x ∈ R;
1 + x2
1
13. (arcctg x) 0 = − , x ∈ R.
1 + x2
V. Dierentiation of basic elementary functions in case that x is replaced
with u(x) where u(x) is an arbitrary dierentiable function on it's domain.
1. (eu(x) ) 0 = eu(x) .u0 (x) ;

2
1  √ 0 1
2. (ln |u(x)|) =
0 0
.u (x), u(x) 6= 0, ln |x + x ± a | = √
2 2 , a = const;
u(x) x ± a2
2

3. (uα (x)) 0 = α.uα−1 (x).u0 (x), α = const;

4. (au(x) ) 0 = au(x) .u0 (x). ln a, x ∈ R, a = const, a > 0, a 6= 1;


1
5. (loga |u(x)|) 0 = .u0 (x), u(x) 6= 0;
u(x). ln a
6. (cos u(x)) 0 = − sin u(x).u0 (x);

7. (sin u(x)) 0 = cos u(x).u0 (x);


1 π
8. (tg u(x)) 0 = .u 0
(x), x 6
= (2k + 1) , k = 0, ±1, ±2, . . .;
cos2 u(x) 2
1
9. (ctg u(x)) 0 = − 2 .u0 (x), u(x) 6= kπ, k = 0, ±1, ±2, . . .;
sin u(x)
1
10. (arcsin u(x)) 0 = p .u0 (x), u(x) ∈ (−1, 1);
1− u2 (x)
1
11. (arccos u(x)) 0 = − p .u0 (x), u(x) ∈ (−1, 1);
1− u2 (x)
1
12. (arctg u(x)) 0 = 2
.u0 (x);
1 + u (x)
1
13. (arcctg u(x)) 0 = − .u0 (x).
1 + u2 (x)
VI. Logarithmic derivative. Let u(x) and v(x) be dierentiable functions on the
set D, moreover let u(x) > 0 on D. Then the function F (x) = u(x)v(x) is dierentiable
function on D and holds the formula
0 0
F 0 (x) = u(x)v(x) = ev(x). ln u(x) = ev(x). ln u(x) .(v(x). ln u(x))0 =

u0 (x)
 
v(x) 0
= u(x) . v (x). ln u(x) + v(x). .
u(x)

3
Some formulas and tables for indenite integrals
0. Denition and properties of the indenite integral:
Z
1. F (x) = f (x) dx + C ⇐⇒ F 0 (x) = f (x) ⇐⇒ dF (x) = f (x) dx;
Z Z Z
2. αf (x) + βg(x) dx = α f (x) dx + β g(x) dx for any constants α and β and
functions f (x) and g(x) ;
Z Z
3. F (x) = f (u(x))u0 (x) dx and G(u) = f (u) du + C then

F (x) = G(u(x)) + C

I. Tables of integrals
I. a) Basic integrals
Z Z
1. 0 dx = C = const., 1 dx = x + C, x ∈ (−∞, ∞) ;
Z
xα+1
2. xα dx = + C, α 6= −1;
α+1
Z
1
3. dx = ln |x| + C, x 6= 0 (the case α = −1);
x
Z
4. ex dx = ex + C, x ∈ (−∞, ∞);
Z
ax
5. x
a dx = + C, x ∈ (−∞, ∞), a > 0, a 6= 1;
ln a
Z
6. cos x dx = sin x + C, x ∈ (−∞, ∞);
Z
7. sin x dx = − cos x + C, x ∈ (−∞, ∞);
Z
1 π
8. dx = tan x + C, x 6
= (2k + 1) , k = ±1, ±2, . . .;
cos2 x 2
Z
1
9. dx = − cot x + C, x 6= kπ, k = ±1, ±2, . . .;
sin2 x
Z
1
10. √ dx = arcsin x + C = − arccos x + C, x ∈ (−1, 1);
1 − x2
1
Z
11. dx = arctan x + C = −arccotgx + C, x ∈ (−∞, ∞);
1 + x2
Z
1 √
12. √ 2 dx = ln |x + x2 + a| + C, x > −a, a = const.;
x +a
I.b) Here we suppose that u(x) is a dierentiable function on it's domain.
Z Z
1. u0 (x) dx = d u(x) = u(x) + C ;
Z Z
u(x)α+1
2. u(x)α u0 (x) dx = u(x)α du(x) = + C, α 6= −1;
α+1
Z
u0 (x) Z
1
3. dx = du(x) = ln |u(x)| + C, u(x) 6= 0 (the case α = −1);
u(x) u(x)
Z Z
4. eu(x) u0 (x) dx = eu(x) du(x) = eu(x) + C ;
Z Z
au(x)
5. au(x) u0 (x) dx = au(x) du(x) = + C;
ln a
Z Z
6. cos u(x)u0 (x) dx = cos u(x) du(x) = sin u(x) + C ;
Z Z
7. sin u(x)u0 (x) dx = sin u(x) du(x) = − cos u(x) + C ;
Z
u0 (x) Z
1
8. 2
dx = 2
du(x) = tan u(x) + C ;
cos u(x) cos u(x)
Z
u0 (x) Z
1
9. 2 dx = 2 du(x) = − cot u(x) + C ;
sin u(x) sin u(x)
Z
u0 (x) Z
1
10. q dx = q du(x) = arcsin u(x) + C = − arccos u(x) + C ;
1 − u2 (x) 1 − u2 (x)
Z
u0 (x) Z
1
11. 2
dx = du(x) = arctan u(x) + C = −arccotgu(x ) + C;
1 + u (x) 1 + u2 (x)
Z
u0 (x) Z
1 q
12. q dx = q du(x) = ln |u(x) + u2 (x) + a| + C
u(x)2 +a u2 (x) +a
III. Integration by parts: If u(x) and v(x) have derivatives on their domains
then holds the formula
Z Z Z Z
0
u(x)v (x) dx = u(x) dv(x) = u(x)v(x) − v(x) du(x) = u(x)v(x) − v(x)u0 (x) dx = . . . .

IV. Change of variables:


If Z Z
F (x) = f (x) dx and G(t) = f (ϕ(t))ϕ0 (t) dt + C
where x = ϕ0 (t) 6= 0 on it's domain then
F (x) = G(ϕ−1 (x)) + C where t = ϕ−1 (x ) is an inverse function of x = ϕ(t).

You might also like